3D Modeling in Elementary Schools and its Use in Testing Creativity - Fadrhonc, Mgr. Jan; Honzíková, Prof. Dr. Jarmila; Tomášková, Ing. Tetjana (3D Modeling in Elementary Schools and its Use in Testing Creativity, 2025)
Creative thinking is the key to adapting new technologies to serve human needs. Creative thinking is essential in education because it prepares students for a rapidly changing world full of complex problems and new challenges. It develops the ability to think critically, seek innovative solutions and adapt to change. It is very important for education today that modern technologies are used in a creative way. The present publication addresses the issue of implementing 3D modeling into primary school teaching. First, the reader is introduced to the basic concepts, then to the 3D modeling technologies of SketchUp. Based on the needs of contemporary education, a brief methodology for teaching 3D modeling is presented, on which pilot and primary research is then based. Due to the lack of a standardized tool for evaluating 3D models, a modification of the Urban Figural Test of Creative Thinking, which was originally designed to evaluate paper-based drawings, was undertaken. The reader will also find the results of verifying this modified creative thinking test in practice in the publication. In a school setting, creative thinking increases student motivation and engagement by allowing them to actively participate in the learning process, which is why it is so important.